Efektivitas Bakteri Amilolitik Asal Geopark Merangin Jambi terhadap Patogenitas Jamur Pyricularia oryzae Penyebab Penyakit Blas Daun Padi - Ummi Mardhiah Batubara; Suparjo Suparjo; Hasnaul Maritsa; Nanda Fahmuin Tari; Selvi Andriani (BIO-SITE |Biologi dan Sains Terapan, 2017)
Rice (Oryza sativa) is a major crop product in Asia. Rice products are increasing along with the increasing of human population. Blast disease in leaf (leaf blast) is the major pathogen in rice during vegetative phase. The using of amylolytic bacteria isolated from Geopark Merangin Jambi is done as an attempt to discover biocontrol agents in order to attack infection of Pyricularia oryzae, the cause of leaf blast disease. Antimicrobial activity assay was carried out by isolating the pathogen in the infected rice crops. Pyricularia oryzae that had been cultured then were evaluated their antagonistic activity against amylolytic bacteria isolated from prior experiment. Results have shown that from 25 isolates of amylolytic bacteria taken from Geopark Merangin Jambi, 2 isolates that can be used as biocontrol agents were GM20 and GM23 capable of inhibiting the growth of Pyricularia oryzae.